2008
DOI: 10.1002/apj.187
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of solvent‐free polylactic‐glycolic acid (PLGA) scaffolds for tissue engineering

Abstract: Conventional methods for fabricating polymeric scaffolds often use organic solvents which might be harmful to cells or tissues. The purpose of this report was to develop a solvent-free method for the fabrication of threedimensional scaffolds for tissue engineering. To manufacture a scaffold, polylactide-polyglycolide (PLGA) copolymers were premixed with sodium chloride particulates. The mixture was then compression molded and sintered to form a cylinder. After sintering, the cylinder was submerged in water for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In this regard, similar results were observed in other studies (Oki et al, 2004;Sharifi et al, 2016). Moreover, other investigations indicated that an increase in the stabilization temperature led to a reduction in the number of hydroxyl groups in the chemical composition of BGNPs, which are necessary for the nucleation of hydroxyapatite-like layers, and for reducing the bioactivity potential of synthesized particles (Hench et al, 1998;Kokubo, 2008;Liu et al, 2009).…”
Section: Characterization Of Bgnpssupporting
confidence: 88%
“…In this regard, similar results were observed in other studies (Oki et al, 2004;Sharifi et al, 2016). Moreover, other investigations indicated that an increase in the stabilization temperature led to a reduction in the number of hydroxyl groups in the chemical composition of BGNPs, which are necessary for the nucleation of hydroxyapatite-like layers, and for reducing the bioactivity potential of synthesized particles (Hench et al, 1998;Kokubo, 2008;Liu et al, 2009).…”
Section: Characterization Of Bgnpssupporting
confidence: 88%
“…The glasses synthesized by sol–gel naturally contained hydroxyl groups in their networks . Based on other investigation, the number of hydroxyl groups decreased with increasing the stabilization temperature . The results demonstrate that the optimal temperature for completion of reactions and stabilization is 600 and 700 °C, respectively.…”
Section: Resultsmentioning
confidence: 70%
“…[25] Therefore, the porosity of artificial scaffolds for tissue engineering is of importance. Different techniques such as porogene leaching, [26,27] gas foaming, [28] phase separation, [29] and 3D printing [30] have been performed to fabricate scaffolds with porous structure. Recently, a new method combining electrospinning and self-assembly was shown to fabricate low-density 3D open cellular scaffold with hierarchical pore size to mimic natural sponge structure.…”
Section: Introductionmentioning
confidence: 99%